Experiencing the Tangible Past through Virtual Reconstruction: Cultural Heritage of Buildings and their Environmental Boundaries - Navvab, Mojtaba; BISEGNA, FABIO; GUGLIERMETTI, FRANCO (Archeomatica, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–> Accurate reconstruction and representation of cultural heritage buildings within virtual environment using auralization and visualization techniques are presented. Given the state of art in computer graphics ability to meet the multidimensional level of demands by cultural heritage fields of studies, it is possible to reconstruct and experience the audio and visual conditions of the past with high degree of realism and share the understanding of our cultural heritage through the interpretation by the experts, historian and or obtain an individual perspective in which past buildings and selected or designated sites by UNESCO were experienced by centuries old generations.